Challenges in the development of analytical test procedure for aminoglycosides: A critical review - Radhakrishnan Hari, Shaik Taherunnisa, Sushil Yadaorao Raut, Srinivas Mutalik, Kunnatur B. Koteshwara (Journal of Applied Pharmaceutical Science, 2019)
The present article reviews the challenges and hurdles in the development of an analytical method for aminoglycosides (AG). The article emphasizes on the attempts made to develop analytical methods based on HPLC and other sophisticated techniques, such as LC-MS, radioimmunoassay, microbial assay, enzyme linked immunosorbent assay (ELISA), extractive colorimetry, anion-exchange chromatography with pulsed amperometric detection, high performance thin layer chromatography, densitometry, and microbial agar diffusion assay. The various media mostly used for the in vitro as well as in vivo estimation of AG by HPLC and LC-MS are heptafluorobutyric acid, ammonium acetate, ammonium formate and formic acid. Estimation of AG by radioimmunoassay and ELISA can be suitably done by using TRIS-HCl and saline phosphate buffer. The buffer media used for ex vivo analysis mostly include MEM, TRIS and saline phosphate. The presence of AG in food from the animal sources, water bodies, and its prolonged exposure may result in serious health issues. The present article outlined the various sensitive, robust and precise analytical techniques for the estimation of the various aminoglycosides in many sources, and discussed the hurdles faced during the development of the analytical techniques.
Keywords: Aminoglycosides, antibiotics, analytical methods, impurities.